CircASH2L Promotes Ovarian Cancer Tumorigenesis, Angiogenesis, and Lymphangiogenesis by Regulating the miR-665/VEGFA Axis as a Competing Endogenous RNA - Chen, Jinxin; Li, Xiaocen; Yang, Lu; Li, Mengmeng; Zhang, Ye; Zhang, Jingru (Frontiers in Cell and Developmental Biology, 2020)
Ovarian cancer is the leading cause of gynecologic cancer-related deaths. Emerging research has revealed a close relationship between circular RNAs (circRNAs) and ovarian cancer development, metastasis, and prognosis. The objective of our research was to further explore the relationship between circASH2L and ovarian cancer. Quantitative real-time polymerase chain reaction was used to detect the differential expression of circRNAs between normal ovaries and ovarian cancer tissues. The impact of circASH2L on the proliferation, invasion, and tumorigenicity of ovarian cancer cells was evaluated using gain- and loss-of-function experiments. The molecular mechanisms of circASH2L function were investigated using bioinformatics analysis, RNA fluorescence in situ hybridization, western blots, and dual-luciferase reporter assays. The results showed that circASH2L was remarkably upregulated in ovarian cancer. The invasion and growth of ovarian cancer cells were suppressed by circASH2L knockdown in vitro, and downregulation of circASH2L restrained both angiogenesis and lymphangiogenesis of tumor xenografts in vivo. Furthermore, circASH2L was mostly distributed in the cytoplasm, where it competes with vascular endothelial growth factor A (VEGFA) for binding to miR-665. These findings indicate that circASH2L has an oncogenic function in ovarian cancer. In conclusion, circASH2L plays a critical role in regulating ovarian cancer cell tumorigenesis, angiogenesis, and lymphangiogenesis through the miR-665/VEGFA axis and, therefore, is a possible candidate target for ovarian cancer treatment.